Myths, perceptions knowledge, attitudes, and practices (KAP) linked to mycobacterial infection management among the pastoralist communities of Uganda - Kankya, C.; Mugisha, A.; Muwonge, A.; Skjerve, E.; Kyomugisha, E.; Oloya, J. (Advance Tropical Medicine and Public Health International, 2011)
The present study was conducted to assess community myths, perceptions, knowledge, attitudes, practices (KAP) of the pastoral farmers and explore mycobacterial infection management practices. Both structured questionnaire survey and participatory rural appraisal approaches were used. This study revealed that mycobacterial infection especially tuberculosis as referred to in vernacular as akakonko, akasubba or akafuba because of the persistent cough and other respiratory symptoms. Knowledge attitudes and practices: congestion under extended family homes, sharing of household utensils, consumption of untreated milk and drinking untreated water as means of mycobacterial infections spread to humans. Perceptions: sharing the drinking straws and cigarette sticks. Community myths: witchcraft, family history and genetic heritability. Mycobacterial infections and Human Immunodeficiency Virus-Acquired immunodeficiency syndrome (HIV/AIDS) were closely linked and these infections issued stigmatisation among the community members. Mycobacterial infection management methods: Sixty five percent (65 %) of the respondents visited traditional healers and used local herbs while 35% visited health centres and used modern medicines. The multivariate model identified sex, marital status, and age influencing the choice of managing mycobacterial infections. Sustainable community intervention require a thorough understanding of traditional indigenous knowledge, attitudes, practices myths, beliefs and perceptions in designing disease prevention and control strategies at the human- environment-animal interface in the pastoral ecosystems of Uganda.
Keywords: Knowledge; Mycobacterial infections; Participatory methods; Pastoral communities; Uganda